Novel Computed Tomography-based Metric Reliably Estimates bone Strength, Offering Potentially Meaningful Enhancement in Clinical Fracture Risk Prediction - Shah,SIMRANA; Jin,ANDI; Wilson,HANNAHCP; Abel,PAULD; Price,PATRICIAM; Hansen,ULRICHN; Abel,RICHARDL (European Journal of Medicine, 2015)
Osteoporosis with resultant fractures is a major global health problem with huge socioeconomicimplications for patients, families and healthcare services. Areal (2D bone mineraldensity (BMD) assessment is commonly used for predicting such fracture risk, but is unreliable,estimating only about 50% of bone strength. By contrast, computed tomography (CT) basedtechniques could provide improved metrics for estimating bone strength such as bone volumefraction (BVF; a 3D volumetric measure of mineralised bone), enabling cheap, safe and reliablestrategies for clinical application, and to help divert resources to patients identified as most likelyto benefit, meeting an unmet need.Here we describe a novel method for measuring BVF at clinical-CT like low-resolution(550µm voxel size). Femoral heads (n=8) were micro-CT scanned ex-vivo. Micro-CT data weredowngraded in resolution from 30µm to 550µm voxel size and BVF calculated at high and lowresolution. Experimental mechanical testing was applied to measure ex vivo bone strength ofsamples. BVF measures collected at high-resolution showed high correlation (correlationcoefficient r2=0.95) with low-resolution data. Low-resolution BVF metrics showed high correlation(r2=0.96) with calculated sample strength. These results demonstrate that measuring BVF at lowresolution is feasible, which also predicts bone strength. Measures of BVF should be useful for clinically estimating bone strength and fracture risk. The method needs to be validated using clinical CT scans.